2021
DOI: 10.1111/tbed.14165
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study revealing host‐associated genetic signatures for source attribution of sporadic Campylobacter jejuni infection in Egypt

Abstract: Campylobacter jejuni (C. jejuni), is considered among the most common bacterial causes of human bacterial gastroenteritis worldwide. The epidemiology and the transmission dynamics of campylobacteriosis in Egypt remain poorly defined due to the limited use of high-resolution typing methods. In this pilot study, we evaluated the discriminatory power of multiple typing 'gene-by-gene based' techniques to characterize C. jejuni obtained from different sources and estimate the relative contribution of different pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…In Egypt, farming practices often lack adequate biosecurity and regulation. Only limited studies have reported the prevalence and distribution of Campylobacter in Egyptian campylobacteriosis cases [4], and little is known about the dominant source reservoirs driving infection and transmission [20]. In Europe, potential source reservoirs have been identified through source attribution studies, with poultry products regarded as the primary source of infection [6, 21–23].…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, farming practices often lack adequate biosecurity and regulation. Only limited studies have reported the prevalence and distribution of Campylobacter in Egyptian campylobacteriosis cases [4], and little is known about the dominant source reservoirs driving infection and transmission [20]. In Europe, potential source reservoirs have been identified through source attribution studies, with poultry products regarded as the primary source of infection [6, 21–23].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the rate of Campylobacter infections in human population in Egypt, several previous studies documented that Campylobacterios is an important cause of diarrhea in children in the country (39)(40)(41). In this respect, up to 85% of children in Egypt were found infected with Campylobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Another population genetic method for source attribution is STRUCTURE (Jehanne et al, 2020 ; Mughini-Gras et al, 2021 ; Mulder et al, 2020 ; Saif et al, 2022 ). STRUCTURE uses model-based clustering, which assigns a cluster (population) to each sample, while simultaneously estimating the allele frequency in each population (Pritchard et al, 2000 ).…”
Section: Microbiological Source Attributionmentioning
confidence: 99%